Economic Policy Uncertainty and Financial Innovation: Is There Any Affiliation? - Jia, Zeng; Mehta, Ahmed Muneeb; Qamruzzaman, Md.; Ali, Majid (Frontiers in Psychology, 2021)
The impetus of this study is to gauge the nexus between economic policy uncertainty (EPU) and financial innovation in Brazil, Russia, India, China, and South Africa (BRIC) nations for the period from 2004M1 to 2018M12. This study utilizes both the linear and non-linear autoregressive distributed lag (ARDL) models to evaluate the long-run and the short-run association between EPU and financial innovation; furthermore, the causal effects are investigated by following the non-Granger casualty framework. The results of long-run cointegration, i.e., the test statistics of modified F-test (FPSS), standard Wald test (WPSS), and tBDM, reject the null hypothesis and establish the presence of the long-run association between EPU and financial innovation. Conversely, long-run asymmetry cointegration revealed the test statistics of FPSS, WPSS, and tBDM in non-linear estimation. Furthermore, both in the long run and short run, the Wald test results disclose asymmetric effects running from EPU to financial innovation. In regards to the asymmetric impact of EPU on financial innovation, this study documents that the positive and negative shocks in EPU are negatively linked with financial innovation in the long run but are insignificant for short-run effects. Besides, financial innovation measured by R&D investment exhibits a positive linkage with shocks in EPU, implying that uncertainty induces innovation in the economy. Referring to causality effects, this study divulges the feedback hypothesis, i.e., bidirectional causality prevails between EPU and financial innovation in all sample countries.